Generalizations in Analogical Argument - Zhu, Wensheng; Huang, Huaxin (Informal Logic, 2025)
This paper presents a generalization-centered framework for analyzing analogical arguments. By examining how analogical generalization is treated across various research paradigms, it highlights its role in modeling both similarity and relevance. Unlike deductive or inductive generalizations, analogical generalization is empirical, hypothetical, and context-sensitive, underscoring the sui generis nature of analogical arguments. Building on this foundation, the paper extends the classical scheme and introduces a set of critical questions anchored in generalization. A detailed case study illustrates the framework’s practical value in identifying argument structure, modeling context sensitivity, and assessing the cogency of analogical arguments.